DECISION ACCOUNTING. - Beckert, Ralph F.; Grawoig, Dennis E. (The Accounting Review, 1965)
Abstract The complexity of today's business environment has motivated many researchers in mathematics and the management sciences to search for and experiment with devices and techniques designed to increase the effectiveness of decision making. This quest for new methodologies has been spurred on by the increased usage of electronic computers since the large data out-put of EDP systems is difficult to absorb and interpret with conventional methods. This research has been implemented by a number of important advances in the fields of applied mathematics and statistics. An important group of techniques have appeared recently utilizing mathematics and statistics as one approach to optimal or at least more effective problem solving. Many of the methods developed are of significant potential value to the accounting profession. And, likewise, many of today's accounting techniques could be successfully integrated with the emerging body of mathematical methods. Accounting educators have the opportunity presently to provide business with a new type of specialist versed both in accounting and mathematical methods.